Nanomechanical clinical coagulation diagnostics and monitoring of therapies. Issue 45 (10th November 2017) - Padovani, Francesco; Duffy, James; Hegner, Martin
Abstract : Nanoscillations of microcantilevers as a novel strategy to diagnose and monitor blood coagulation disorders, using a few microliters of the sample. Abstract : Clinical coagulation diagnostics often requires multiple tests. Coagulation times are a first indication of an abnormal coagulation process, such as a coagulation factor deficiency. To determine the specific deficient factor, additional immuno- and/or enzyme assays are necessary. Currently, every clinical laboratory has to normalize their assays (international normalized ratio, INR), and therefore, certain variability within the clinical analytics exists. We report a novel strategy for a quick, reliable and quantitative diagnosis of blood coagulation diseases ( e.g. haemophilia) and for monitoring factor replacement and anticoagulant therapies ( e.g. heparin treatment). We exploit nano-oscillations of microcantilevers for real-time measurements of the evolving blood plasma clot strength (viscosity). The sensors are oscillated at multiple high resonance mode numbers, in order to minimise the oscillation amplitude (a few nanometers), to provide direct internal control and to increase the quality factor. Along with the activated thromboplastin time (aPTT) and prothrombin time (PT) other parameters important for thrombosis diagnostics can be obtained, including the final clot strength and the fibrinolysis time. We demonstrate the dependence of the parameters on factor deficiencies and we diagnose a specific factor deficiency through an integrated and quantitative in situ immunoassay. This approach does not require continuous calibration since it delivers an absolute quantity (clot strength). The low sample volume required (a few μl) and the ability to measure different parameters within the same test (PT, aPTT and global coagulation assay) make the presented technique a versatile point-of-care device for clinical coagulation diagnostics.